Reconstruction of Village Authority Regulations in Implementing Village Government in a State Constitutional System Based on Pancasila Justice Values - Suratno, Suratno; Gunarto, Gunarto; Prasetyo, Teguh (Indonesian Journal of Advanced Research, 2025)
Pancasila as the basis of the state plays a fundamental role in village government. Although it is constitutionally recognized through Law No. 6 of 2014, village government practices still face challenges such as overlapping authority, weak institutions, and subordination to local governments. This study uses a socio-legal approach with qualitative methods through interviews, observations, and literature studies in Wirogunan Village, Kartasura, Sukoharjo. The results of the research reconstruct the values and norms of village authority to be in harmony with Pancasila, especially in the management of tourism, water resources, and fisheries. This reconstruction emphasizes the importance of environmental ethics, citizen participation, and social justice, and places villages as autonomous entities and main actors of sustainable development within the framework of the Republic of Indonesia.